ANALISIS PERBANDINGAN ALGORITMA KRIPTOGRAFI METODE DATA ENCRYPTION STANDARD DENGAN METODE ADVANCED ENCRYPTION SYSTEM : STUDI KASUS PADA PT. ONE STANDARD GROUP PTE LTD - Akhmad Budi; Arabella Chicali (Jurnal Informatika dan Bisnis, 2019)
The security system within a company is the top priority, one of its application is in web media, where it exist various confidential information in it, such as user information on the company PT. One Standard Group PTE LTD must be kept confidential not to fall into unauthorized parties, therefore a security system to address the information security is needed. The security system of modern symmetric key cryptography algorithms is considered to be able to overcome these problems which are generally divided into two, namely Data Encryption Standard (DES) dan Advanced Encryption System (AES). From the two algorithms, the author makes comparisons to obtain a more efficient algorithm in terms of security and times. The method that the author used in this research is Extreme Programming Research Methodology, with a qualitative methodological analysis technique, and in data collection author uses direct observation and literature study. The system that the author created applies additional security for user information which will be directly stored with the AES method and the DES method and the system will display the processing time of both. The conclusion that the author can achieve from this thesis is AES method cryptographic algorithms are more secure than the DES method because the AES method has double protection, but from the time aspect efficiency, the DES method cryptographic algorithms are more efficient. Keyword: Data Security, Cryptographic, AES, DES